Scutellaria baicalensis targets the hypoxia‐inducible factor‐1α and enhances cisplatin efficacy in ovarian cancer. Issue 9 (24th May 2018) - Hussain, Imran; Waheed, Sana; Ahmad, Kashif A.; Pirog, John E.; Syed, Viqar
Abstract: Hypoxia‐inducible factor‐1alpha (HIF‐1α) is aberrantly upregulated in tumors and implicated in angiogenesis, metastasis, and drug resistance. Therefore, developing treatments that target HIF‐1α may be a viable therapeutic approach. In Traditional Chinese Medicine (TCM), Scutellaria baicalensis (SB) is used for the treatment of cancer but the anti‐cancer mechanisms are not known. We examined the effects of SB on HIF‐1α expression in ovarian cancer (OC) cell lines grown under normoxic and hypoxic conditions. SB treatment attenuated HIF‐1α expression in cancer cell lines. Treatment of cells with cycloheximide (CHX) reduced HIF‐1α levels similar to cells treated with SB. Furthermore, SB‐induced HIF‐1α inhibition was abrogated by the proteasomal inhibitor MG132 and a lysosome inhibitor, chloroquine. Activation of PI3K/AKT and MAPK/ERK seen in OC cells was reduced with SB. Pretreatment of cells with LY294002 (phosphoinositide 3‐kinase inhibitor) and PD98059 (mitogen‐activated protein kinase inhibitor) reduced HIF‐1α expression comparable to SB‐treated cells. SB potentiated the anti‐growth effects of cisplatin on OC cells by attenuating the expression of HIF‐1α, ABCG1, and ABCG2. Taken together, the findings suggest that targeting HIF‐1α with SB could be an effective treatment strategy for cancer and SB can improve the sensitivity of cancer cells to cisplatin, which is a major challenge in therapy for ovarian tumors. Abstract : Combination of SB and cisplatin is more effective in inhibiting proliferation of cisplatin sensitive and resistant ovarian cancer cells compared to treatment with SB or cisplatin alone.